(untitled) (Journal of Pedagogical Inventions and Practices, 2023)
This article considers the use of information technology in Russian language lessons. The use of technical means at various lessons has a significant impact on the organization of students’ activities. Also, information technologies play a great role in the learning process, qualitatively changes the process and results of learning.